In-situ confined construction of N-doped compact bamboo charcoal composites for supercapacitors. (June 2023) - Zhang, Ziqiang; Li, Yudong; Yang, Xuemiao; Han, Enshan; Chen, Gaojun; Yan, Caihong; Yang, Xiaohui; Zhou, Desheng; He, Yanzhen
Abstract: Preparing carbon-based electrode materials from biomass is an important research direction at present. Here, through in-situ polymerization of polypyrrole (PPy) system in bamboo cells and reconstruction of the micromorphology of carbon materials by filling functional materials, the purpose of uniform nitrogen doping and morphological filling is realized, while maintaining excellent cell pore structure. In addition, PPy lines and bamboo cell walls combined to form a dual morphology, and formed a microporous network structure during carbonization, which increased the specific surface area of carbon materials (2420.6 m 2  g −1 ) and increased the content of N element (1.59 %). Compared with pure bamboo (189.0 F g −1 ) and PPy lines (297.7 F g −1 ), the PPy/bamboo charcoal exhibits a specific capacitance of 403.2 F g −1 and 217.73 F cm −3 with the energy density of 17.60 Wh kg −1 at a power density of 250 W kg −1, which is better than common bio-derived materials. This work presents a potential in-situ and cheap synthesis strategy in the bamboo cell to construct energy devices. Graphical abstract: Unlabelled Image Highlights: PPy with special morphologies were in-situ and uniformly constructed in bamboo cells. Carbonation PPy-L improved the internal structure of bamboo-derived carbon. The PC/NC-L excellent capacitance performance, high power density and high energy density